Non-corrosive and low-cost synthesis of hierarchically porous carbon frameworks for high-performance lithium-ion capacitors. (March 2021) - Qian, Tong; Huang, Yunchun; Zhang, Mengdi; Xia, Zhengzheng; Liu, Haiyan; Guan, Lu; Hu, Han; Wu, Mingbo
Abstract: Because of their capability of rapid lithium uptake/release and robust capacitive energy storage, hierarchically porous carbon frameworks are widely regarded as promising electrode materials for lithium-ion capacitors. The current technologies for their syntheses involve either a heavily corrosive KOH activation or harsh template-removing processes exerting heavy environmental burdens. To surmount these drawbacks, we, herein, report the production of such an architecture by simply carbonizing petroleum asphalt with KHCO3 contributing to hierarchically porous frameworks with high specific surface area in a non-corrosive condition. The microporous carbon nanosheets are curved to give mesopores and interconnected for macropores. Because of these structural merits, the rate-capable lithium storage is realized and the capacitive performance is three-times higher than that of widely used activated carbon cathodes. Furthermore, the lithium-ion capacitors simultaneously using these materials as the anode and cathode can deliver a high energy density of 112 Wh kg -1 at a power density of 260 W kg − and present an energy density of 48 Wh kg −1 at a high-power density of 52 kW kg -1 . The versatile capabilities provided by the mild and low-cost carbon materials may find an alternative strategy for the real application of lithium-ion capacitors and other hybrid devices. Graphical abstract: Benefiting from the structural merits and facile synthesis process, the assembled full-carbon LIC using the hierarchically porous carbon nanosheets as anode and cathode displays a maximum energy and power density of 112 Wh kg −1 and 52 kW kg −1, respectively, showing great potential for a wealth of hybrid energy storage devices. Image 1